Criticism of the HAS Opinion of July 21st, 2022, on Maintaining of the SARS-Cov-2 Vaccine Mandate for Healthcare Workers - Sainton, Jérôme (Coronaviruses, 2023)
The opinion of the French National Authority for Health (HAS) on July 21st, 2022, concluded that the mechanism of the SARS-Cov-2 vaccine mandate for caregivers and other health professionals should be maintained. Constructed as a syllogism, the opinion states that the benefit-risk balance of a three-dose vaccination schedule to limit transmission is favorable (major premise) and that this balance necessarily determines the mechanism of SARS-Cov-2 vaccine mandate (minor premise) so that it should be maintained (conclusion). Each of these steps is flawed. First, the benefit-risk analysis of a three-dose vaccination schedule is many times distorted: it fails to transpose the relative efficacy of the vaccination in terms of absolute efficacy; it fails to take into account both the particularly poor efficacy of the vaccination against the risk of infection (symptomatic or not) and its decrease, or even negativation, over time, as well as the worsening of the vaccine escape with the latest Omicron sub-lineages; it does not assess the risk associated with the mechanism, particularly with regard to COVID convalescents and pregnant women. Secondly, the inference made from this analysis to the specific mechanism of mandatory vaccination of caregivers is distorted. There is no refocusing on the specific population of caregivers, and the real and concrete benefit of the mechanism itself is not measured. Thirdly, the very construction of the reasoning is distorted. By reducing a medical problem to the calibration of a strictly technical benefit- risk balance, it evades the intrinsic practical and ethical dimensions of the issue.
Keywords: fallacies